Genetic variability of Tropical Milking Criollo cattle of Mexico estimated from genealogy information - Ponce, Adalberto Rosendo; Palacios Jiménez, Ana L.; Rosales Martínez, Froylan; Torres Hernández, Glafiro; Ramírez Valverde, Rodolfo; Becerril Pérez, Carlos M. (Revista Colombiana de Ciencias Pecuarias, 2018)
Background: Genetic variability of populations is essential for their genetic conservation and improvement, and genealogy analysis is a useful tool to estimate it. Objective: To determine genetic variability and inbreeding levels in Tropical Milking Criollo (LT). Methods: This study analyzed the genealogy of LT using the ENDOG software. Registration certificates of 3,427 LT animals born between 1945 and 2013, and from 608 born between 1950 and 2013 were used. Two populations were defined: the first one with all registered animals (PLT), and the second with nucleus animals (PCP). Results: Estimates for PLT and PCP were: founders 890, 114; ancestors 855, 102; effective founders 111, 43; effective ancestors 72, 26, and effective population size 68.1 and 64.6, respectively. Inbreeding coefficients were 4.32 and 3.48% for the highest genetic integrity index; and the average relatedness (AR) coefficients were 1.19 and 5.55 for PLT and PCP, respectively. Genealogy depth was shallow in both populations, with full equivalent generations of 2.00 and 3.53. Global generation intervals were about seven years. Conclusions: The LT population is not endangered and its genetic improvement program should continue.